Gastric Carcinomas With Lymphoid Stroma: An Evaluation of the Histopathologic and Molecular Features. (April 2018) - Hissong, Erika; Ramrattan, Girish; Zhang, Pan; Zhou, Xi Kathy; Young, Gloria; Klimstra, David S.; Shia, Jinru; Fernandes, Helen; Yantiss, Rhonda K.
Abstract : Gastric carcinoma with lymphoid stroma is an uncommon variant enriched for mutually exclusive Epstein-Barr virus (EBV) positivity and mismatch repair (MMR) deficiency. We performed this study to evaluate molecular alterations in this morphologically homogeneous subtype and compare them with 295 conventional gastric cancers analyzed in The Cancer Genome Atlas study. We identified 31 study cases and subjected them to in situ hybridization for EBV-encoded RNAs and assessment for MMR status. Immunostains for PD-L1, β-catenin, and HER2 were performed; extracted DNA was sequenced with a Comprehensive Cancer Panel. Most study patients were older adult men with stage I or II disease (76%). Tumors were classified as EBV + /MMR-proficient (MMR-P) (n=7), EBV − /MMR deficient (n=12), and EBV − /MMR-P (n=12). EBV − /MMR-P tumors were usually located in the proximal stomach (83%) and showed heterogenous growth patterns with glandular differentiation (83%). Tumors in all groups showed numerous tumor infiltrating lymphocytes and PD-L1 expression, infrequent nuclear β-catenin accumulation (10%), and lacked both membranous HER2 staining and HER2 amplification. EBV − /MMR-deficient tumors showed significantly higher tumor mutation burden ( P =0.001) and KRAS alterations (56%) compared with EBV − /MMR-P tumors (9%, P =0.05). TP53 variants were more common among EBV − /MMR-P tumors (82%) compared with EBV + /MMR proficient (0%, P =0.01) and EBV − /MMR-deficient (11%, P <0.01) tumors. Alterations in KRAS, ARID1A, PIK3CA, and TP53 followed similar patterns of distribution compared with The Cancer Genome Atlas dataset. We conclude that gastric carcinomas with lymphoid stroma show a spectrum of molecular changes and frequent PD-L1 expression, raising the possibility that this subgroup of tumors may be susceptible to checkpoint inhibitors and/or agents that target receptor tyrosine kinase-mediated signaling.